2013
DOI: 10.1007/s00572-013-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives

Abstract: Medicinal plants have been used world-wide for thousands of years and are widely recognized as having high healing but minor toxic side effects. The scarcity and increasing demand for medicinal plants and their products have promoted the development of artificial cultivation of medicinal plants. Currently, one of the prominent issues in medicinal cultivation systems is the unstable quality of the products. Arbuscular mycorrhiza (AM) affects secondary metabolism and the production of active ingredients of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0
8

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 51 publications
4
88
0
8
Order By: Relevance
“…or on other plant taxa (Kapoor et al 2004;Liu et al 2007;Jurkiewicz et al 2010;Zubek et al 2012). In addition, the effects of AM fungi on the secondary metabolite (SM) production and storage in MAPs, of which the economic importance often relies upon their SM content and concentration, differed depending on the chemical classes, nutrient availability for the plant, AM fungus used in the experiment, and botanical taxon of the host plant (Brundrett 2009;Zeng et al 2013;Bona et al 2016b). In particular, it was shown that AM fungi can increase the content and concentration of SMs either by mediating nutrient uptake, mostly P, involved in the biosynthetic pathways of SMs (Kapoor et al 2004) or irrespective of any effect on P uptake (Khaosaad et al 2006;Nell et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…or on other plant taxa (Kapoor et al 2004;Liu et al 2007;Jurkiewicz et al 2010;Zubek et al 2012). In addition, the effects of AM fungi on the secondary metabolite (SM) production and storage in MAPs, of which the economic importance often relies upon their SM content and concentration, differed depending on the chemical classes, nutrient availability for the plant, AM fungus used in the experiment, and botanical taxon of the host plant (Brundrett 2009;Zeng et al 2013;Bona et al 2016b). In particular, it was shown that AM fungi can increase the content and concentration of SMs either by mediating nutrient uptake, mostly P, involved in the biosynthetic pathways of SMs (Kapoor et al 2004) or irrespective of any effect on P uptake (Khaosaad et al 2006;Nell et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The advantages of AM symbiosis to host plants have been demonstrated extensively in terms of enhancement of plant biomass and nutrient uptake, especially in cereals and legumes (Kaschuk et al 2010;Saia et al 2015a;Pellegrino et al 2015;Bona et al 2016a). In medicinal and aromatic plants (MAPs), most of the information about the effects of AM fungi has been derived from investigations about the family Lamiaceae (Khaosaad et al 2006;Copetta et al 2006;Zeng et al 2013;López-García et al 2014;Bona et al 2016b; Silvia Lazzara and Marcello Militello equally contributed to this work.…”
Section: Introductionmentioning
confidence: 99%
“…This is because mutual benefits are particularly reinforced under extreme environmental conditions [9]. These symbioses also increase production of secondary metabolites in medicinal plants [3]. Stevia rebaudiana inoculated with AMF can produce higher concentrations of steviol glycosides compared to non-AMF inoculated plants; it can stimulate an uptake of nutrients, as well as increase chlorophyll and carbohydrate concentrations that directly result in biomass improvement [10].…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizae fungi (AMFs) can form symbiotic relationships with the vast majority of land plants, enhance biomass and growth rates, improve stress resistance, stimulate mineral nutrients uptake and raise photosynthesis of the infected plants [1][2][3]. For instance, P uptake and growth parameters of cowpea plants were positively influenced by AMFs inoculation under a medium or low P fertilization treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the increasing demand for plants utilized in the herbal industry, recent research has emphasized the development of new techniques to improve the quality and quantity of plant material obtained from agricultural production. These techniques to enhance the biomass and standards of medicinal plants may include the proper management of indigenous arbuscular mycorrhizal fungi (AMF) and the inoculation of plants with AMF during cultivation (Gianinazzi et al 2010;Zeng et al 2013). AMF have been found to stimulate growth, improve resistance to pathogens, heavy metals and salinity, and influence the level of secondary metabolites in plants (Smith and Read 2008).…”
mentioning
confidence: 99%